Comparison of Prognostic Scores in Patients With Hepatocellular Carcinoma Treated With Sorafenib. Issue 1 (14th January 2021) - Sansone, Vito; Tovoli, Francesco; Casadei-Gardini, Andrea; Di Costanzo, Giovan Giuseppe; Magini, Giulia; Sacco, Rodolfo; Pressiani, Tiziana; Trevisani, Franco; Rimini, Margherita; Tortora, Raffaella; Nardi, Elena; Ielasi, Luca; et al.
Abstract : INTRODUCTION: Prognostic classifications for patients treated with sorafenib for hepatocellular carcinoma (HCC) facilitate stratification in trials and inform clinical decision making. Recently, 3 different prognostic models (hepatoma arterial-embolization prognosis [HAP] score, sorafenib advanced HCC prognosis [SAP] score, and Prediction Of Survival in Advanced Sorafenib-treated HCC [PROSASH]-II) have been proposed specifically for patients treated with sorafenib. This study aimed to compare the prognostic performance of different scores. METHODS: We analyzed a large prospective database gathering data of 552 patients treated with sorafenib from 7 Italian centers. The performance of the HAP, SAP, and PROSASH–II models were compared with those of generic HCC prognostic models (including the Barcelona Clinic for Liver Cancer and Italian Liver Cancer staging systems, albumin–bilirubin grade, and Child-Pugh score) to verify whether they could provide additional information. RESULTS: The PROSASH-II model improved discrimination (C-index 0.62) compared with existing prognostic scores (C-index ≤0.59). Its stratification significantly discriminated patients, with a median overall survival of 21.5, 15.3, 9.3, and 6.0 months for risk group 1, 2, 3, and 4, respectively. The HAP and SAP score were also validated but with a poorer performance compared with the PROSASH-II. DISCUSSION: Although suboptimal, PROSASH-II is the most effective prognostic classification model among other available scores in a large Italian population of patients treated with sorafenib.